2014
DOI: 10.1108/mip-01-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of satisfaction and revisit intentions for full-service restaurants

Abstract: Purpose – The purpose of this paper is to identify the antecedents of satisfaction and revisit intentions for full-service restaurants. The economic crisis is known to have had a deep impact on consumer behavior with regards to restaurants and this study is primarily focussed on exploring the effects on the traditional antecedents of satisfaction and revisit intentions as full-time restaurants attempt to reposition their offer. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 81 publications
8
59
0
12
Order By: Relevance
“…Customers' perceptions of service quality have been studied by many scholars and practitioners who have shown that they are positively related to satisfaction (Marinkovic et al, 2014;Baber et al, 2011;Berry and Wall, 2007;Cronin et al, 2000;Farrell et al, 2001;Berry et al, 2006). Some scholars believe that satisfaction is determined by a cognitive process, being…”
Section: Customer Perception and Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Customers' perceptions of service quality have been studied by many scholars and practitioners who have shown that they are positively related to satisfaction (Marinkovic et al, 2014;Baber et al, 2011;Berry and Wall, 2007;Cronin et al, 2000;Farrell et al, 2001;Berry et al, 2006). Some scholars believe that satisfaction is determined by a cognitive process, being…”
Section: Customer Perception and Customer Satisfactionmentioning
confidence: 99%
“…Marinkovic et al (2014) believe that the restaurant business relies on factors that are constantly responding to changes in social and economic status. In that situation, restaurants may have to consider their strategy to match customer preferences in order to satisfy customers with a quality service, which may help organizations to gain more customers with their favourable intentions.…”
mentioning
confidence: 99%
“…In contrast to the ideal-typical approach, we propose that revisit intention should be captured at destination point with actual tourists. This approach has been adopted by prior revisit intention studies (Guntoro & Hui 2013;Marinkovic et al 2014). To bridge the gap in the eWOM, intention to revisit, destination trust and gender literature, this study offers an integrated approach to examine the interplay of the aforementioned variables.…”
Section: Introductionmentioning
confidence: 99%
“…Niat berobat ulang sebuah produk/jasa merupakan tanggapan emosional berupa kesiapan bertindak sebagai hasil penaksiran kognitif sebuah kejadian (Frijda, 1988;Bagozzi, et al, 1999;Clore & Ortony, 2000 kepuasan (Amin & Nasharuddin, 2013;Marinkovic et al, 2014;Bonn et al, 2016;Su et al, 2016), kualitas pelayanan (Cronin et al, 2000;Su et al, 2016), dan harga (Marinkovic et al, 2014). Lee et al, (2000) Dalam perspektif emosi, kepuasan merupakan hasil evaluasi kognitif yang menimbulkan tanggapan emosional (Frijda, 1988;Bagozzi, et al, 1999;Clore & Ortony, 2000).…”
Section: Niat Berobat Ulangunclassified
“…Hubungan antar konstruk dalam Hal yang mengejutkan adalah pada umumnya pengaruh kepuasan konsumen pada niat berkunjung ulang/berobat ulang selalu terkomfirmasi (Cronin et al, 2000;Mittal & Kamakura, 2001;Amin & Nasharuddin, 2013;Marinkovic et al, 2014;dan Su et al, 2016) …”
Section: Teknik Analisis Dataunclassified